JUST: a measure of jury system trustworthiness - Bornstein, Brian H. (Psychology, crime & law, 2020)
Three studies developed and tested a new measure of the perceived trustworthiness of the jury system, the 23-item Jury System Trustworthiness (JUST) scale, and assessed the scale’s convergent and discriminant validity. Study 1 assessed the scale’s factor structure and relation to other relevant constructs. In Studies 2 and 3, the JUST scale was administered to participants in two separate mock juror studies. The results of all three studies supported the hypothesized factor structure of the measure but showed that a simplified, 7-item measure was also effective. Overall, participants’ perceptions of juries were moderately positive, and the JUST scale was related to attitudes toward the police, authoritarianism, belief in a just world, juror bias, preference for a jury (vs. a bench) trial, and intention to respond to a jury summons. It also explained a unique portion of the variance in jury-specific beliefs and behavioral intentions, such as preference for a jury trial and response to a summons, beyond that accounted for by other legal attitudes. The JUST scale was not related to verdict decisions in either mock trial after controlling for authoritarianism. Several individual differences (e.g. age, race/ethnicity) were also related to attitudes toward the jury system.